Improving Fine Motor Skills of Cerebral Palsy Children Through Maze Game Media - Faisal Rachmat; Yufiarti; Hapidin (Proceeding of International Conference on Islamic Boarding School, 2025)
The Maze game media helps children develop their fine motor abilities, such as flexing their fingers and wrists, as well as fine motor skills related to both hands’ movement capabilities and the capacity to combine eye awareness and hand activity. The purpose of this study is to examine how effective maze game media enhances fine motor abilities in children with Cerebral Palsy aged 3 to 8 years at the Type D South Jakarta Disability School. This research utilizes an action research methodology. Action research is a cyclical methodology focused on diverse acts or interventions implemented by researchers in their capacity as classroom educators. The research encompassed the design phase through to the assessment of practical classroom interventions aimed at improving the fine motor abilities of students affected by cerebral palsy. During the 2023-2024 academic year, researchers examined children’s fine motor skills through labyrinth game media in the classroom. The research was conducted in three phases: the pre-cycle, cycle 1, and cycle 2. The results of the researh revealed that regression of fine motor skills through maze game media is 0.926 (R2: 0.858). Meanwhile, the improvement of fine motor skills of children with Cerebral Palsy through the maze game media obtained significant results based on the T count α 0.05, which is -2.394, which is greater than the T Table (1.812461) so that there is an increase in fine motor skills of children with Cerebral Palsy through the media, the maze game is effectively negative or tends to be low